LAWS EXEGESIS VERSUS JURISPRUDENCE (Comparative Studies in Understanding Religious Text and the Istinbath Process of Law on Mahar) - Muammar Muhammad Bakry (JICSA : Journal of Islamic Civilization in Southeast Asian, 2020)
Fiqh and Tafsir Ahkam are basic courses at the Faculty of Usuluddin and the Faculty of Sharia. These two disciplines of science are the products of ulama's legal thinking whose objects are different but inseparable from one another. Faqih (fiqh expert) and mufassir (interpreter) can sit together to solve the legal problems faced by people with their respective approaches and methods. In this paper, these two disciplines are discussed with various perspectives. Epistemologically has its own specifications, and axiologically has their respective roles in answering the problems of humanity.